IMPROVING FINANCIAL CONTROL: THE CONTRIBUTION OF ACCOUNTING INFORMATION SYSTEMS TO SMALL BUSINESS PERFORMANCE - Lili Syafitri; Andi Primafira Bumandava Eka; Asry Ady Bakri; Aslichah Aslichah; Iwan Henri Kusnadi (SEAN Institute, 2023)
Small businesses play a crucial role in the economy, but confront complex obstacles such as limited resources, limited access to markets and capital, and difficulties with financial control. Their success depends on sound financial management. However, small businesses frequently struggle with financial management due to error-prone manual processes and inaccurate data. Therefore, the objective of this study is to implement an Accounting Information System as a viable means of enhancing the financial control and performance of small businesses. The research provides recommendations for accounting information system characteristics that effectively align with the business procedures of small businesses. In the modern business era, there are 18 functional requirements analyses that can be implemented as accounting information system features to improve the financial control and performance of small enterprises.